Penerapan Pendekatan Deep Learning untuk Mendukung Pembelajaran Matematika di Sekolah Dasar - Engelina Nababan; Salwa Huda Muliana Hasibuan; Sonya Mika; Tasya Amanda Putri; Elvi Mailani; Nur Rarastika (Lembag, 2025)
This study discusses how to apply a deep learning approach to support mathematics learning in elementary schools. Where this study uses a qualitative method. This study obtains data from literature reviews, researchers examine various relevant national scientific sources to identify the benefits, challenges, and opportunities for integrating deep learning technology in mathematics learning. The results of the study show that the application of deep learning to mathematics studies has a positive impact on student understanding. This method encourages active student involvement through various interactive activities, such as simulations and experiments, so that the learning process becomes more meaningful and enjoyable. However, the application of this method is also faced with a number of challenges, such as limited time to complete the curriculum and unequal access to technology among students.